HMGA2-mediated epigenetic regulation of Gata6 controls epithelial canonical WNT signaling during lung development and homeostasis - Singh, Indrabahadur; Justus Liebig University Giessen (My University, 2014)
Organ regeneration requires a proper balance between self-renewal and differentiation of tissuespecific progenitor cells. Progenitor cell expansion and differentiation recapitulate many of the mechanisms regulating embryonic development. The high-mobility-group (HMG) proteins are the most abundant non-histone chromatin-associated proteins. They are present at high levels in various undifferentiated tissues during embryonic development and their levels are strongly reduced in the corresponding adult tissues, where they have been implicated in maintaining and activating stem/progenitor cells. Here, this study uncovered the role of the high mobility group AT-hook protein 2 (HMGA2) as a key regulator of branching morphogenesis and epithelial differentiation during embryonic lung development as well as in adult lung. Detailed analysis of the Hmga2 knockout (Hmga2-/-, KO) mice together with in vitro Hmga2 loss-of-function (LOF) experiments revealed enhanced canonical WNT signaling resulting not only in defective lung epithelial differentiation but also in increased numbers of bronchioalveolar stem cells (BASCs). Increased numbers of progenitor cells in the lung of Hmga2-/- mice generated an imbalance in cell differentiation that is reflected in a reduction of alveolar type II (ATII) cells, thereby affecting both lung morphology as well as lung functionality. It also showed that HMGA2 directly regulates Gata6 which is crucial for fine-tuning canonical WNT signaling in airway epithelium.In addition, this study deciphered the molecular mechanism of transcriptional activation mediated by HMGA2. It showed that Hmga2-induced transcriptional activation of Gata6 requires phosphorylation of the linker histone H1 at S65 (H1S65ph) and the core histone variant H2AX at S139 (H2AXS139ph), both mediated by the kinase, ataxia telangiectasia mutated (ATM). It also demonstrated the sequential order of events in which H1S65ph precedes H2AXS139ph and both are a prerequisite for the subsequent disassembly of promoter-associated nucleosomes and transcriptional activation. The functional interplay between HMGA2, ATM, H1 and H2AX is a novel mechanism of transcription initiation.Together, this data demonstrate that HMGA2-mediated changes in chromatin structure regulate canonical WNT signaling and control the balance between progenitor cells expansion and differentiation required for both lung development and homeostasis.

Die Regeneration von Organen bedarf einer physiologischen Balance zwischen Selbsterneuerung und Ausdifferenzierung von gewebespezifischen Vorläuferzellen, wobei die Expansion und Ausdifferenzierung dieser Vorläuferzellen zahlreiche Regulationsmechanismen der Embryonalentwicklung verlangt.High mobility group (HMG)-Proteine sind die häufigsten Vertreter innerhalb der Gruppe des Nicht-Histon-Chromatins assoziierten Proteine und treten verstärkt in verschiedenen, undifferenzierten Geweben während der Embryonalentwicklung auf. Im entsprechenden adulten Gewebe sind diese nur noch geringfügig vorhanden und für die Aufrechterhaltung und Aktivierung von Stamm- oder Vorläuferzellen verantwortlich. In der vorliegenden Studie wurde die Rolle des high mobility group AT-hook Proteins 2 (HMGA2) als Schlüsselmolekül während der Morphogenese, sowie während der Ausdifferenzierung des Epithels in der embryonalen als auch in der adulten Lunge beschrieben. Durch detaillierte Analyse der Lunge von Hmga2-/-Mäusen in Kombination mit Experimenten ohne funktionierendes Hmga2 konnte eine verstärkte Signaltransduktion des kanonischen WNT-Signalwegs festgestellt werden, die nicht nur zur fehlerhaften Ausdifferenzierung des Epithels, sondern auch zu einem erhöhten Vorkommen von Bronchoalveolaren Stammzellen (BASCs) in der adulten Lunge führte. Durch die erhöhte Anzahl von Vorläuferzellen in den Lungen von Hmga2-/- Mäusen veränderte sich das Gleichgewicht zwischen Selbsterneuerung und Ausdifferenzierung, was in einer verminderten Anzahl von Typ2 Pneumozyten (ATII) resultierte und eine veränderte Lungenmorphologie, sowie Funktionalität zur Folge hat. Weiterhin zeigte, dass HMGA2 ein direkter Regulator von Gata6 ist, der eine entscheidende Transkcriptionsfaktor in der WNT-Signaltransduktion ist. Insgesamt konnte eine direkte transkriptionale Aktivierung von Gata6 durch HMGA2 beobachtet werden, wobei diese Aktivierung abhängig von der Phosphorylierung von S65 (H1S65ph) an Histon H1 sowie von S139 (H2AXS139ph) an Histon H2AX durch die Kinase Ataxia telangiectasia mutated (ATM) ist. Hierbei folgt H2AXS139ph auf H1S65ph und erst im Anschluss finden der Abbau von Promoter-assoziierten Nukleosomen und die transkriptionale Aktivierung statt. Diese Interaktionen von HMGA2, ATM, H1 und H2AX zeigen einen neuen Mechanismus für die Initiation der Transkription.Zusammengefasst, demonstriert die vorliegende Studie, dass HMGA2-vermittelte Veränderungen in der Chromatinstruktur die kanonische WNT-Signaltransduktion regulieren, wodurch das physiologische Gleichgewicht zwischen Expansion oder Differenzierung von Vorläuferzellen in Balance gehalten wird, was entscheidend für die Lungenentwicklung als auch für die Homöostase ist.
Keywords: HMGA2; lung development; Gata6; H2Ax; epigenetics; ddc:570